Pengembangan Media Pembelajaran Interaktif Berbasis Android untuk Pengajaran Fi’il di Kelas 10 Madrasah Aliyah - Lutpiasari, Lutpiasari (Universitas Suryakancana, 2025)
This article describes the development steps of interactive learning media based on android for Arabic language instruction. The research approach employs both qualitative and quantitative methods. The development steps for the learning media follow the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The software used includes Microsoft PowerPoint, Ispring Suite 10, and Web2Apk Builder. The research findings indicate that the Android-based interactive learning media offers flexible learning opportunities, can be accessed without an internet connection, and enhances students' interest in learning Arabic. The trial conducted with 10th-grade students at Madrasah Aliyah yielded a score of 92%, falling within the range of 80-100%, which is categorized as